Association between miRNA‐196a2 rs11614913 T>C polymorphism and Kawasaki disease susceptibility in southern Chinese children. Issue 7 (26th May 2019) - Wang, Jinxin; Li, Jiawen; Qiu, Huixian; Zeng, Lanlan; Zheng, Hao; Rong, Xing; Jiang, Zhiyong; Gu, Xueping; Gu, Xiaoqiong; Chu, Maoping
Abstract: Background: miRNAs play important roles in a variety of diseases. Thus, the association between miRNA‐196a2 rs11614913 T>C polymorphism and Kawasaki disease susceptibility is still unknown. Methods: We included 532 children with Kawasaki disease and 623 healthy children from South China, and their DNA was extracted for genotyping by TaqMan methodology. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to estimate the strength of association. Results: No significant associations were observed between the miRNA‐196a2 rs11614913 T>C polymorphisms and Kawasaki disease risk (TC vs TT: adjusted OR = 1.04, 95% CI = 0.79‐1.37; CC vs TT: adjusted OR = 0.87, 95% CI = 0.63‐1.21; dominant model: adjusted OR = 0.99, 95% CI = 0.76‐1.27; and recessive model: adjusted OR = 0.85, 95% CI = 0.64‐1.13). There was also no significant correlation found in stratified analyses. Conclusion: This study suggests that miRNA‐196a2 rs11614913 T>C may not be associated with Kawasaki disease susceptibility in a southern Chinese population. Larger, multicenter studies are needed to confirm our conclusions.